MEDIASI DALAM PANDANGAN HUKUM PROGRESIF Suatu Alternatif Penyelesaian Konflik Keluarga - Kamaruddin Kamaruddin (Al-'Adl, 2018)
Mediation is a process of negotiation in solving a problem, where certain parties or third parties do not take sides, and cooperate with the disputing parties to seek an agreement to end the problem. And the mediator does not have the authority to decide disputes, but solely helps the parties to resolve problems that have been entrusted to him. Mediation in the view of progressive law is one of the strategies in resolving all the complexities of the problems faced to ensure happiness and human well-being that is full of desires and hopes in resolving conflicts for humanity and humanity.